Intelligent Nano-tech Switch for Advanced Automated Plant Growth Regulation - Das, Supankar; Mittal, S K; Dogra, Amit; Singh, Deepika; Dubey, K K; Singh, Bikar; Shivling, V D (Journal of Agricultural Engineering, 2014)
Precise control of plant growth is important to know the effect of external growth factors on crop yield. A nano-tech switch mechanism automaticallyoperated by plant stem expansion was designed to control the major external growth factors for plant such as light and water level in soil. Nano level expansion of stem produced by the dynamism of fluid (water) uptake by stimulation of sunlight is measured using laser interferometry to determine the elasticity of switch. Switching parameter was determined by nano level growth characteristics which were mathematically correlated with fluid flow rate and elastic property of the stem. Supply of two major external growth factors in irrigation system were controlled intelegently by plant morphological and physical response, which are dependent on other major and minor growth factors and with their variable combinations. The methodology is useful in irrigation system.